Holographic Imaging Using an Imperfect Plane Wave Illumination With a Background Phase - Li, Rujia; Yang, Feng; Cao, Liangcai (Frontiers in Physics, 2022)
Aberrations in the optical components and misalignments in the optical system cause a background phase in the coherent illumination. To reconstruct the object phase, the background phase illuminating the object must be measured and subtracted. For diffraction imaging and in-line holography, the traditional phase retrieval method reconstructs the phase diffracting from clear edges. However, it falls into stagnation when solving a background phase slowly varying in the spatial domain. In this study, we propose to solve the background phase using a modulation-based phase retrieval method. Alternative structured phase modulation (ASPM) can be the phase constraint to avoid stagnation when solving the background phase without clear edges. With ASPM, the background phase in the experiment can be efficiently retrieved when 16 phase patterns are employed. The ASPM acts as a phase grating to concentrate the intensities and provides robustness to noise. Compared to the conventional random phase modulations, the ASPM method had a smaller error value in the reconstruction iterations, which leads to a better reconstruction quality. After measuring and subtracting the background phase, the object phase was retrieved using a coherent diffraction imaging system. A phase plate can be accurately reconstructed under three different background phases.